2014
DOI: 10.5489/cuaj.1240
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A is not detectable in renal and testicular tumours

Abstract: Introduction: Ochratoxin-A (OTA) is one of the most abundant food-contaminating mycotoxins, known for its nephrotoxicity, neurotoxicity, gonadotoxicity, teratogenicity, immunosuppression and carcinogenesis. OTA has been linked to several genitourinary pathologies, including Balkan nephropathy and genitourinary malignancies. We examine OTA levels in serum samples and tumour specimens collected from patients with renal and testicular tumours. Methods: Frozen samples were obtained from the Ontario Tumour Bank. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Indeed, a 15 years study confirmed that BEN is correlated with upper urothelial tract cancer (Rouprêt et al, 2015 ). Furthermore, OTA has been associated with the occurrence of upper urothelial tract cancer (Fahmy et al, 2014 ). However, a systemic review by Bui-Klimke and Wu ( 2015 ) revealed that there is no significant evidence for human health risks associated with OTA exposure based on the epidemiological data.…”
Section: Gastrointestinal Tractmentioning
confidence: 99%
“…Indeed, a 15 years study confirmed that BEN is correlated with upper urothelial tract cancer (Rouprêt et al, 2015 ). Furthermore, OTA has been associated with the occurrence of upper urothelial tract cancer (Fahmy et al, 2014 ). However, a systemic review by Bui-Klimke and Wu ( 2015 ) revealed that there is no significant evidence for human health risks associated with OTA exposure based on the epidemiological data.…”
Section: Gastrointestinal Tractmentioning
confidence: 99%
“…Dietary exposure to AFB 1 may induce abdominal pain, vomiting, hepatitis, and hepatocellular carcinoma [ 16 ] in consumers. OTA can cause renal toxicity including genito-urinary malignancy [ 17 ]. Therefore, to improve food safety, it is important to monitor mycotoxins in dried seafood products sold at markets.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, reiteration of [13] in [28] perpetuated the focus on the equivalence of “germ cell testicular tumours in mice and humans,” without any corroborative histological evidence. More recently, analysis for OTA in archived blood plasma and testicular germ cell human tumours [29] found traces of the toxin in plasma but not in tumour histology. That finding does not take into account that histology solvents would remove OTA.…”
Section: Discussionmentioning
confidence: 99%